PS-B05-3: CARDIOVASCULAR RESPONSES EVOKED BY LOW ENERGY CONTINUOUS VERSUS INTERMITTENT STIMULATION OF THE AORTIC BARORECEPTOR AFFERENTS IN HYPERTENSION. (January 2023) - Salman, Ibrahim M; Ameer, Omar Z; McMurray, Sheridan; Hassan, Sarah F; Sridhar, Arun; Lewis, Stephen J; Hsieh, Yee Hsee
Abstract : Objectives: Device-based neurostimulation of the carotid baroreceptors is a novel approach to control hypertension. We have previously demonstrated the significance of aortic baroreceptor afferent nerves as a viable alternative neuromodulation target to carotid baroreceptors in lowering mean arterial pressure (MAP) in hypertension. We have also shown that appreciable reductions in MAP do not necessarily require the use of ultrahigh stimulation parameters. In this study, we aimed to investigate if energy consumption for neuromodulation of aortic baroreceptor afferents could be lowered further by using intermittent as opposed to continuous stimulation. Design and method: In male anesthetized spontaneously hypertensive rats (SHRs), the effects of continuous (20 sec) versus intermittent (5 sec ON/3 sec OFF and 5 sec ON/5 sec OFF for 20 sec) stimulation of the left aortic depressor nerve (ADN) on MAP, heart rate (HR), mesenteric (MVR) and femoral (FVR) vascular resistance were assessed using low (5 Hz) and high (15 Hz) frequencies delivered at 0.4 mA and 0.2 ms. Results: Continuous and intermittent low frequency stimulation produced similar sustained decreases in MAP, HR, MVR and FVR. Continuous high frequency stimulation produced larger reductions in MAP, HR, MVR and FVR compared with all low frequency and/or intermittent high frequency stimulations. Conclusions: Low charge intermittent stimulation of the aortic baroreceptor afferents maintains the required reductions in MAP levels in hypertension and intermittent delivery of the electrical stimulus can further lower energy consumption for neuromodulation. Clinically, these findings may provide useful insight for studies using baroreflex modulation in resistant hypertension and other cardiovascular diseases.